Preparing Students for Technical Creativity in Extracurricular Activities: Methodology and Approaches (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Technical creativity plays a crucial role in developing students' problem-solving abilities, innovation, and adaptability in the rapidly evolving technological landscape. This article explores effective methodologies for preparing students for technical creativity through extracurricular activities. It examines theoretical foundations, pedagogical strategies, and practical implementations that enhance students' engagement in creative technical work. The article highlights the role of project-based learning, mentorship, interdisciplinary approaches, and the use of modern digital tools in fostering technical creativity. Additionally, challenges and solutions in implementing these methods are discussed.